2010
DOI: 10.4028/www.scientific.net/msf.638-642.1476
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline LPSO Mg-Zn-Y-Al Alloys with High Mechanical Strength and Corrosion Resistance

Abstract: Interests in magnesium alloys increase as eco-material for its lightweight, and many investigations have been carried out on the development of manufacturing processes and alloy development. In 2001, Mg97Zn1Y2 (at%) alloy with a tensile yield strength of 610 MPa and an elongation of more than 5 % has been developed by rapidly solidified powder metallurgy (RS P/M) processing. The developed alloy was characterized by a novel phase with long period stacking ordered (LPSO) structure. Recently, we have investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…After Kawamura et al reported a YS of 610 MPa in the Mg–6.7Y–2.5Zn alloy in 2001 [116], any YS exceeding 600 MPa was not reached in subsequent studies [227229,237,238]. Even when the Mg–6.7Y–2.5Zn alloy was produced by a similar rapid solidification, powder metallurgy and hot extrusion methods, the YS of Mg–6.7Y–2.5Zn alloy was reported to be about 480 MPa [238].…”
Section: Extrusion Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…After Kawamura et al reported a YS of 610 MPa in the Mg–6.7Y–2.5Zn alloy in 2001 [116], any YS exceeding 600 MPa was not reached in subsequent studies [227229,237,238]. Even when the Mg–6.7Y–2.5Zn alloy was produced by a similar rapid solidification, powder metallurgy and hot extrusion methods, the YS of Mg–6.7Y–2.5Zn alloy was reported to be about 480 MPa [238].…”
Section: Extrusion Alloysmentioning
confidence: 99%
“…After Kawamura et al reported a YS of 610 MPa in the Mg–6.7Y–2.5Zn alloy in 2001 [116], any YS exceeding 600 MPa was not reached in subsequent studies [227229,237,238]. Even when the Mg–6.7Y–2.5Zn alloy was produced by a similar rapid solidification, powder metallurgy and hot extrusion methods, the YS of Mg–6.7Y–2.5Zn alloy was reported to be about 480 MPa [238]. For the Mg–Y–Zn alloys produced by conventional casting and hot extrusion, the tensile YSs of as-extruded alloys are found to be even lower, in the range between 200 and 400 MPa [93,227229].…”
Section: Extrusion Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…1214) Therefore, the RS ribbon-consolidated Mg0.85Zn2.05Y0.35Al (at%) alloys could be excellent material choice for aerostructures such as stringers and brackets. 15) In structural design, planestrain fracture toughness is an important property requirement. In our previous study, we demonstrated that a preconsolidation heat treatment of the RS ribbons was effective in improving the ductility and fracture toughness of the Mg 0.85Zn2.05Y0.35Al alloy.…”
Section: Introductionmentioning
confidence: 99%
“…This idea has been applied to Mg-LPSO alloys as well. Several processing techniques, such as powder metallurgy [5,26], extrusion of recycled chips [27,28], equal channel angular pressing [27], rotary swaging technique [29,30] or rapidly solidified (RS) ribbon-consolidation [31][32][33], have been developed to reach the goal of developing the sub-micron grain-sized Mg alloys.…”
Section: Introductionmentioning
confidence: 99%